Applying blockchain technology in Vietnamese logistics service providers: Current situation and development solutions - Pham Thanh Ha; Le Ngoc Hoa; Hoang Thi Hanh; Le Viet Hoang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Blockchain technology has brought transformative changes to a wide range of industries, with the logistics sector being no exception. This paper delves into the practical applications of blockchain among logistics service providers in Vietnam, offering an in-depth analysis of its advantages and the challenges it presents. Furthermore, it outlines strategic solutions to foster the adoption and growth of blockchain within the logistics domain. Findings from research and real-world implementations highlight blockchain's potential to dramatically improve transparency, boost operational efficiency, and reduce costs across Vietnam's logistics supply chain. Code: 24120301